Pre operative radiation for icteric type hepatocellular carcinoma A case report (Faculty of Medicine Universitas Indonesia, 2008)
Hepatocellular Carcinoma (HCC) is still a leading health problem worldwide, due to its correlation with HBV and HCV infection and its management which is strongly dependent on patient's condition and tumor extension. Surgery, with liver resection or liver transplantation offer a good survival rate as a primary management of such cancer. But since liver resection must consider some aspect of liver function and tumor size, and liver transplantation was not a choice in Indonesia, many treatment modalities has been developed which can be used to overcome this problem, such as tumor ablation, transarterial chemo embolization (TACE), chemotherapy and radiotherapy. With the development of conformal radiotherapy, the hepatitis induced radiation therapy could be minimized. This paper present a case of conformal radiation therapy utilization in icteric type HCC in Dr. Cipto Mangunkusumo Hospital, Jakarta. Hepatic resection was planned for this patient. (Med J Indones 2008; 17: 255-8)